ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE PADA FOTO TUGU ASIA AFRIKA DI AKUN INSTAGRAM @BRILLIANFAIRIANDI - Dewi, Rachima Meilani; Fitriawati, Diny (UKRI, 2026)
The Asia Africa Monument is one of the historical monuments in Bandung City which was built to commemorate the important event of the 1955 Asia Africa Conference, as well as being a symbol of the unity of nations in Asia and Africa, the symbolic meaning of this monument can be seen through various media, such as in the photo uploaded by the Instagram account @brillianfairiandi. This study aims to reveal the meaning of the signs contained in the photo of the Asia Africa Monument uploaded by the Instagram account @brillianfairiandi using Charles Sanders Peirce's semiotic theory. The research method used in this study is descriptive qualitative through sign analysis based on Peirce's three main triadic semiotic models, namely Representamen/Sign, Object, and Interpretan/Meaning. Data were obtained through observation or in-depth observation of the photo object, interviews with @brillianfairiandi as the image maker, documentation, and data triangulation or a combination of the three methods. The research results indicate that there are seven signs/objects referred to in this image: the dominant color in the image, the globe at the top of the monument, the text